3(2x+1)=-9x

Simple and best practice solution for 3(2x+1)=-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+1)=-9x equation:



3(2x+1)=-9x
We move all terms to the left:
3(2x+1)-(-9x)=0
We multiply parentheses
6x-(-9x)+3=0
We get rid of parentheses
6x+9x+3=0
We add all the numbers together, and all the variables
15x+3=0
We move all terms containing x to the left, all other terms to the right
15x=-3
x=-3/15
x=-1/5

See similar equations:

| -5t^2+5t+20=t | | 10b+8-6b+16=b-9 | | k+4=-21+6k | | 9x+7=2x-56 | | -6n+18=3(-3n+4) | | 2/3y+(-8)=-12.5y+150 | | 2x+3x-2=2x+16 | | 4=2(g−7) | | 4+4n=4n+2 | | -5t^2+5t+20=0 | | j+25=3 | | 11k+9=1+9k | | 3x+12=-66-10 | | 9+10x=89 | | 7x=314x/6= | | 6p-12=6(2p+4) | | 8k-3=59 | | 1/2(18+20x)=89 | | 7u–9=40 | | -2n+3=-11 | | 2−r=1 | | 13x+4−8=+6x−13x−4 | | .5(2x+4)=6 | | 12g+4=100 | | 6r+1=121 | | 6x+68=180 | | 8q+43=123 | | 4x/3+2=14 | | j=22-14 | | w+2/3=1/5 | | 115=k25 | | j-14=22 |

Equations solver categories